Comparison of Minimally Invasive Plate Osteosynthesis and Intramedullary Nailing for Tibial Shaft Fracture: A Systematic Review and Meta-Analysis - I Wayan Subawa; Anak Agung Ngurah Bagus Surya Darma (GLOBAL HEALTH SCIENCE GROUP, 2025)
Tibia shaft fractures are thought to affect 4% of the elderly population. Both low energy and high energy mechanisms have the potential to damage the tibia. Two frequently utilized surgical procedures that are superior to other available choices (external fixation and conventional plate fixation) for the treatment of tibia shaft fractures are intramedullary nailing (IMN) and minimally invasive plate osteosynthesis (MIPO). We compare minimally invasive plate osteosynthesis versus intramedullary nailing for tibial shaft fracture in terms of return to work, hospital stay, and complications over the duration of 1-2 years of follow-up.Methods: A PRISMA guided systematic review was done. A comprehensive literature search was performed to find study in English comparing between MIPO and IMN for tibial shaft fracture from January 2017 until August 2022. PubMed, Google Scholar, and Cochrane Library. The focus in this systematic review and meta-analysis is to compare outcome between MIPO and IMN for tibial shaft fracture. ((“Minimally Invasive Plate Osteosynthesis”, “Intramedullary Nailing”), AND (“Tibial Shaft Fracture”), AND (“Outcome Measure”)) were utilized in the search.Results: This meta-analysis included a total number of 214 patients with 91 patients undergoing MIPO and 123 patients undergoing IMN. The follow-up period was 1-2 years after the treatment. There were found no significant differences statistically in terms of hostpital stay, return to work, infection, malunion, and non union. Conclusion: Our investigations show that both IMN and MIPO are safe and effective methods in treating tibial shaft fractures, and our results show that both methods provide similar outcomes in length of stay, return to work, infection, malunion, and non-union aspects.